Health Practices of Parents for Their Children at Upper Banks, Poro (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
Everyone begins life with a good sound, healthy body that requires care and maintenance. Knowledge of the body systems and how they interact with one another is important in building and promoting personal health and well-being. When your body is kept in good condition through sound health practices from early childhood, it will surely sustain a high level of personal health later in life. Children represent the future and ensuring their healthy growth and development ought to be a prime concern of all societies. The early years of a child’s life provide the foundation for future health, development and well being. Most parents know the basics of keeping children healthy, like offering them healthy foods, making sure they get enough sleep and exercise and insuring their safety. This study was conducted to determine the health practices of the parents for their children at Upper Banks, Poro, City of San Fernando, La Union. The descriptive developmental research design was used with 20 parents as respondents. About 20% of the respondents are mothers who take care of their children. Most have been married for 6 to 10 years and 25% each of the family has one to three children. There is no significant relationship between profile and health practices. Health Practices along with their dietary consumption, management of illness, and behavioral modalities of their children reveal that parents (frequently/ always) follow them. A health advocacy program was formulated for the parents to enhance their knowledge about taking care of the dietary consumption, management of illness, and behavioral modalities for their children. The health advocacy program was conducted and validated and was considered effective.
Keywords: health practices, practices of parents, health advocacy program